Haploid genetic variation in populations from Uganda, Zambia and the Central African Republic - Barkhan, Debra (My University, 2004)
Y chromosome DNA and mitochondrial DNA (mtDNA) variation were examined in Ugandans, Zambians, Biaka Pygmies and non-Pygmies from the Central African Republic. Y chromosome DNA variation was also examined in populations from the Democratic Republic of Congo. Data generated in this study were analysed together with published data to (1) clarify the understanding of the overall patterns of haploid genetic variation in Africa; (2) examine genetic affinities among central African and other African populations; (3) assess the concordance of haploid markers with different mutation rates in assessing population affinities; (4) compare male and female migration rates in African populations; and (5) refine theories regarding the prehistory of central Africa populations based on linguistics and archaeology. Sixteen biallelic and eight microsatellite Y-specific markers were examined in 369 central African individuals. Eleven Y chromosome haplogroups (HGs A, B*, B-M150, B-Ml 12, B- M211, E-M191, E-M2, E-M35, E-M40, FJ and R) and 174 compound haplotypes were identified. The mtDNA 9-bp deletion, 3592 Hpal and 10397 Alul restriction polymorphisms, and two hypervariable regions (HVRs) were examined in 397 individuals. A total of 246 mtDNA types were identified and classified into 19 mtDNA subhaplogroups. Using Y chromosome data, central African populations shared close genetic affinities with each other and with populations from west and southern Africa. Extensive unidirectional Y chromosome gene flow from non-Pygmy populations to Biaka Pygmies was observed. Using mtDNA data, central African non-Pygmy populations shared close genetic affinities with each other and with populations from west, east and southern Africa. MtDNA studies indicated almost complete maternal genetic isolation of Biaka. Overall, using both mtDNA and Y chromosome data, pan-African populations were best grouped by geographic rather than by linguistic criteria. Different mtDNA and Y chromosome data types revealed similar genetic relationships among African populations. Female migration rates appear to have exceeded male migration rates in non-Pygmy central African populations in this study, whilst the opposite was found in Biaka Pygmies. Data types at different levels of resolution suggested that male and female migration rates in Africa may have differed over time, and may not have been significantly different. This research has provided new insights into the complex demographic history that shaped the present-day genetic landscape of central African populations.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the Degree of Doctor of Philosophy.
Keywords: Haploidy; Genetic Variation